An investigation into the role of attitudes in inhibiting parents from talking about sexuality to their adolescents - Maneli, Desmond Mzwabantu (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil)--University of Stellenbosch, 2011.